Multifaceted roles of ninjurin1 in immunity, cell death, and disease - Zhu, Lili; Xu, Yunfei (Frontiers in Immunology, 2025)
Ninjurin1 (NINJ1) is initially identified as a nerve injury-induced adhesion molecule that facilitates axon growth. It is initially characterized to promote nerve regeneration and mediate the transendothelial transport of monocytes/macrophages associated with neuroinflammation. Recent evidence indicates that NINJ1 mediates plasma membrane rupture (PMR) in lytic cell death. The absence or inhibition of NINJ1 can delay PMR, thereby mitigating the spread of inflammation resulting from cell lysis and preventing the progression of various cell death-related pathologies, suggesting a conserved regulatory mechanism across these processes. Further research elucidated the structural basis and mechanism of NINJ1-mediated PMR. Although the role of NINJ1 in PMR is established, the identity of its activating factors and its implications in diseases remain to be fully explored. This review synthesizes current knowledge regarding the structural basis and mechanism of NINJ1-mediated PMR and discusses its significance and therapeutic targeting potential in inflammatory diseases, neurological disorders, cancer, and vascular injuries.